The approach of revelation of the Quran and al Sunnah to dealing with soul and mental disorders after the COVID-19 outbreak - Masruri, Muhammad; Borham, Abd Shakor; Abdul Rahim, Mohd Hisyam; Sulkhan Chakim, Sulkhan Chakim; Muhammad Faiz, Muhammad Faiz (Human Resource Management Academic Research Society, 2022)
A healthy and fit soul is one of each individual's essential needs in order to interact with the environment and construct a better future. Since the beginning of 2019, the COVID-19 outbreak has spread rapidly worldwide. It has raised concerns and had negative consequences for soul and mental health. This is a serious problem for both individuals and society as a whole. This research tries to describe how mental and mental diseases were treated and dealt with during and after the COVID-19 pandemic from the perspective of the Qur'an and Sunnah as divine Revelations. Islam, being a religion concerned with the wellbeing of the ummah, has provided a teaching principle on how to manage and deal with various soul and mental diseases. This approach is one of the best alternatives that is expected to have a significant impact on achieving a healthy soul in the face of long-term pandemic challenges and conjectures. There are several methods promoted by Islam in treating soul and mental disorders, including; always maintain personal hygiene through taharah, reading or listening of the Quran, practicing halal and healthy eating, taubat (repentance) and istighfar, patience and fasting.